Developmental and behavioral toxicity of citalopram in zebrafish early life stages: Neurochemical alterations, oxidative stress responses, and transcriptomic signatures - Yanhua Liu; Manting Li; Jianqiu Yu; Fanrui Yu; Leilei Lu; Jianqiu Chen; Ruixin Guo (Aquatic Toxicology, 2026)

BOTDR Monitoring of Tensile State in Three-Core Fiber-Optic Composite Submarine Cables with a Three-Layer Mechanical Structure and Dual-Threshold Sensing Model - Manting Guo; Yanpeng Hao; Yashuang Zheng; Busheng Chen; Xin Yu; Licheng Li (Journal of Marine Science and Engineering, 2026)
Submarine cables are critical components for power transmission in offshore wind farms, making their condition monitoring paramount for ensuring operational reliability. Addressing unclear strain transfer and underdeveloped Brillouin optical time-domain reflectometry (BOTDR) sensing models for three-core fiber-optic composite submarine cables, this study investigated a 66 kV cable and clarified a BOTDR monitoring principle based on the three-layer mechanical structure. Using the external optical unit’s average Brillouin shift for temperature compensation, four characteristic parameters (Δvy, Δvp, vm, vF) were analyzed. The results show the optical unit’s tensile strain-induced Brillouin shift exhibits periodic distribution along the cable. The stable average peak vF achieved a correlation coefficient of 0.98 with tensile load Fi. A dual-threshold sensing model was established: no shift response below F0 = 90 kN (7.84% Rated Tensile Strength (RTS)); strong linear correlation between vF and Fi beyond Fm = 110 kN (9.58% RTS) with a tensile sensitivity coefficient of 0.03788 MHz/kN. This study provides key BOTDR technical support for submarine cable tensile monitoring in complex marine environments.

Neurodevelopmental toxicity of black carbon in zebrafish: behavioral and metabolomic insights - Fanrui Yu; Yanhua Liu; Manting Li; Yaqian Gao; Leilei Lu; Jianqiu Chen; Ruixin Guo (Aquatic Toxicology, 2025)

Associations of long-term exposure to fine particulate matter and its components with ovarian aging: Evidence from a cross-sectional study in China - Zifeng Cao; Xinyi Wu; Hongyuan Liu; Keyan Xu; Yehuan Yang; Manting Yang; Daimin Wei; Shidou Zhao; Xue Jiao; Qi Zhao; Ruimin Zheng; Yingying Qin; et al. (Journal of Hazardous Materials, 2025)

Self-assembly of tea polyphenol onto the high strength chitosan film fabricated via a new way to enhance the antioxidant and antibacterial activity for meat preservation - Yuntao Wang; Xiuqin Guo; Zhilong Qin; Rongqin Liu; Shengjie Li; Manting Du; Si Qiu; Yanhong Bai (Food Packaging and Shelf Life, 2025)

Soil organic matter components and sesquioxides integrally regulate aggregate stability and size distribution under erosion and deposition conditions in southern China - Geng Guo; Yu Kong; Yanyin Xu; Xiaoying Peng; Manting Niu; Guangruo Zeng; Zhen Ouyang; Jun Liu; Chen Zhang; Jie Lin (Journal of Hydrology, 2024)

Pharmacokinetic Modeling of the Effect of Tariquidar on Ondansetron Disposition into the Central Nervous System - Manting Chiang; Hyunmoon Back; Jong Bong Lee; Sarah Oh; Tiffany Guo; Simone Girgis; Celine Park; Simon Haroutounian; Leonid Kagan (Pharmaceutical Research, 2024)
Purpose Serotonin (5-HT 3 ) receptor antagonists are promising agents for treatment of neuropathic pain. However, insufficient drug exposure at the central nervous system (CNS) might result in lack of efficacy. The goal of this study was to evaluate the impact of administration of a Pgp inhibitor (tariquidar) on ondansetron exposure in the brain, spinal cord, and cerebrospinal fluid in a wild-type rat model. Methods Ondansetron (10 mg/kg) and tariquidar (7.5 mg/kg) were administered intravenously, plasma and tissue samples were collected and analyzed by HPLC. A mathematical model with brain, spinal cord, cerebrospinal fluid and two systemic disposition compartments was developed to describe the data. Results The results demonstrate that tariquidar at 7.5 mg/kg resulted in a complete inhibition of Pgp efflux of ondansetron in the brain and spinal cord. The compartmental model successfully captured pharmacokinetics of ondansetron in wild type and Pgp knockout (KO) animals receiving the drug alone or in wild type animals receiving the ondansetron and tariquidar combination. Conclusions The study provided important quantitative information on enhancement of CNS exposure to ondansetron using co-administration of Pgp Inhibitor in a rat model, which will be further utilized in conducting a clinical study. Tariquidar co-administration resulted in ondansetron CNS exposure comparable to observed in Pgp KO rats. Results also highlighted the effect of tariquidar on plasma disposition of ondansetron, which may not be dependent on Pgp inhibition, and should be evaluated in future studies.

Pharmacokinetic Modeling of the Impact of P-glycoprotein on Ondansetron Disposition in the Central Nervous System - Manting Chiang; Hyun-moon Back; Jong Bong Lee; Sarah Oh; Tiffany Guo; Simone Girgis; Celine Park; Simon Haroutounian; Leonid Kagan (Pharmaceutical Research, 2020)